Peran Guru dalam Mengevaluasi Program Pembelajaran untuk Meningkatkan Kualitas Belajar Mengajar di MTs Hifzil Quran Medan - Astika, Lilis; Ramadina, Rifda; Lativah, Hafni; Sholih, M.; Nasution , Inom (Lembaga Intelektual Muda (LIM) Maluku, 2024)
This study was conducted to understand the role of teachers in evaluating learning programs to improve the quality of teaching and learning. This research uses a qualitative method, which is an approach that focuses on understanding phenomena from the perspective of the subjects being studied. The research employs interview and observation techniques. Data analysis in this study uses the Huberman method, which consists of three main steps: data reduction, data presentation, and conclusion drawing. The results of the study show that the role of teachers in evaluating learning programs is as evaluators who have the function to identify, assess, and improve the learning programs that have been created and implemented in the classroom during the teaching and learning process. Teachers must also determine whether these learning programs successfully improve the quality of student learning